2019
DOI: 10.1073/pnas.1900804116
|View full text |Cite
|
Sign up to set email alerts
|

A neural signature of pattern separation in the monkey hippocampus

Abstract: The CA3 and dentate gyrus (DG) regions of the hippocampus are considered key for disambiguating sensory inputs from similar experiences in memory, a process termed pattern separation. The neural mechanisms underlying pattern separation, however, have been difficult to compare across species: rodents offer robust recording methods with less human-centric tasks, while humans provide complex behavior with less recording potential. To overcome these limitations, we trained monkeys to perform a visual pattern separ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 45 publications
6
47
1
Order By: Relevance
“…1D, E). Shuffling analysis (see Methods) confirmed that network events cannot arise by chance (Fig 1E, grey bars correspond to shuffled data, ANOVA F (3,25) =30.12, p=4*10 -14 , Bonferroni post-test resting vs. shuffled p=2.2*10 -10 indicated with asterisk, running vs. shuffled p=1). Simultaneous imaging of MPP and GC activity showed that network events were strongly correlated with MPP activity increases (Fig.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…1D, E). Shuffling analysis (see Methods) confirmed that network events cannot arise by chance (Fig 1E, grey bars correspond to shuffled data, ANOVA F (3,25) =30.12, p=4*10 -14 , Bonferroni post-test resting vs. shuffled p=2.2*10 -10 indicated with asterisk, running vs. shuffled p=1). Simultaneous imaging of MPP and GC activity showed that network events were strongly correlated with MPP activity increases (Fig.…”
mentioning
confidence: 59%
“…This capability requires the animal to generate dissimilar neuronal representations from overlapping input states that represent similar but not identical environments 1 . Such an operation, termed pattern separation, has been ascribed to the hippocampal dentate gyrus in species ranging from rodents to humans [2][3][4] . In the dentate gyrus, polysensory inputs are mapped onto a large number of granule cells which exhibit extremely sparse firing patterns, resulting in a high probability of non-overlapping output patterns [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, both gaze reinstatement (35; see also, ref. 60) and other retrieval-related EM effects (61)(62)(63) have been linked to activity in the hippocampus. Considered together with the present results, these findings suggest that the outcome of behavioral pattern completion (i.e., lure false alarms) may be attributed, at least in part, to the hippocampally mediated reactivation of relational information, reflected, and likely supported by gaze reinstatement.…”
Section: Discussionmentioning
confidence: 99%
“…The dentate gyrus (DG)-CA3 circuit in dHC is thought to play a critical role in resolving overlapping contextual information to distinguish between certain and ambiguous threats (Besnard and Sahay, 2016;McHugh et al, 2007). At the neural level, this may be accomplished by pattern separation, a mechanism by which similar inputs are made divergent at the level of output (Berron et al, 2016;Besnard and Sahay, 2016;Deng et al, 2013;Lee et al, 2015;Leutgeb et al, 2007;Madar et al, 2019aMadar et al, , 2019bMcAvoy et al, 2016;Miller and Sahay, 2019;Neunuebel and Knierim, 2014;Sakon and Suzuki, 2019). Intriguingly, CA1 appears to be less sensitive to contextual discrimination and pattern separation, raising the question of how DG-CA3 computations resolving overlapping contextual information are propagated to extrahippocampal circuits without being modified or undone in CA1 (Knierim and Neunuebel, 2016;Leutgeb et al, 2004;Vazdarjanova and Guzowski, 2004;Yassa and Stark, 2011).…”
Section: Introductionmentioning
confidence: 99%